3D filter material and preparation method thereof

Through hot press composite technology, the multi-layer fiber layer is integrated into the composite end, which solves the problem of the excessive hot press composite area of ​​the existing 3D filter materials, resulting in the reduction of dust capacity, and achieves the improvement of high dust capacity and liquid absorption performance.

CN119567666AActive Publication Date: 2025-03-07ZHEJIANG SHENGLAN NEW MATERIAL&TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411624424.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The area required for existing 3D filter materials during hot pressing composite is too large, resulting in a decrease in dust capacity, and the use of adhesives to composite will affect the liquid absorption performance.

Method used

The multi-layer fiber layer is integrated into the composite end by using hot pressing composite technology, avoiding the use of adhesive, and the composite end and filter end are formed by hot pressing and composite of flower rolls, significantly reducing the area of ​​the hot pressing composite.

Benefits of technology

It significantly improves the dust capacity and liquid absorption performance of 3D filter materials, while ensuring the composite strength and avoiding the barrier interface problems caused by adhesive composite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134335470000071
    Figure BDA0005134335470000071
  • Figure BDA0005134335470000081
    Figure BDA0005134335470000081
Patent Text Reader

Abstract

The invention relates to the technical field of filter materials, and discloses a 3D filter material and a preparation method thereof.The 3D filter material comprises a composite end and a filter end adjacent to the composite end, the filter end comprises a plurality of stacked fiber layers, the composite end is formed by hot-pressing and compositing the fiber layers, and the multiple fiber layers are composited into a whole through the composite end of the material. Parts which are not pressed are not affected, the problem that the dust holding capacity and the liquid absorption performance of the 3D filtering material are reduced due to the fact that an adhesive is used for compounding can be avoided, and the material has high compounding strength and high dust holding capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of filter materials, and in particular to a 3D filter material and a preparation method thereof. Background Art

[0002] 3D filter materials are usually used to separate water and other substances, such as wipes, absorbent pads in sanitary materials, filter elements of oil-water separators, etc. They are three-dimensional structures with dense pore structures composed of fibers. When the 3D filter material is in use, water molecules are absorbed into the fiber gaps through the capillary action formed by the pore structure between fibers, thereby separating water from other substances. The 3D filter material only collects water through the pore structure, and the water in the 3D filter material needs to be discharged later. Therefore, the pore structure between the fibers of the 3D filter material and the space ratio formed have a greater influence on the water content it can accommodate.

[0003] The fibers of the 3D filter materials in the prior art mainly include natural cotton fibers and polyester fibers. However, the natural cotton fibers have poor high temperature resistance and acid and alkali resistance and cannot be used in high temperature and acid and alkali environments. Although the polyester fibers have strong high temperature resistance and acid and alkali resistance, they are less soft than natural cotton fibers. Therefore, in order to make the 3D filter materials have multiple functions such as high temperature resistance, acid and alkali resistance and softness, fibers with different functions are usually compounded, such as the technical solutions of CN112726058A and CN102162173B. Since the properties of fibers with different functions are quite different, the strength after compounding is low, and the 3D material is easily broken. Therefore, the prior art uses adhesives for bonding and compounding, but the adhesive will easily form a barrier interface after use, resulting in a decrease in the liquid absorption performance of the 3D filter material. In addition, the prior art also proposes to modify the fibers and then use hot pressing compounding to compound the modified fibers, but different fibers still have the problem of poor compatibility and low composite strength. Therefore, it is also necessary to increase the hot pressing compound area to increase the composite strength, but too large a hot pressing compound area will lead to a decrease in the dust holding capacity of the 3D filter material. Therefore, how to ensure the composite strength while reducing the hot pressing compound area is of great significance to increasing the dust holding capacity of the 3D filter material. Summary of the invention

[0004] In order to overcome the problem of large hot-pressed composite area and small dust holding capacity of 3D filter materials in the prior art, the present invention provides a 3D filter material and a preparation method thereof. The material includes a composite end and a filter end adjacent to the composite end. The composite end is made by hot-pressing composite. The composite end composites multiple fiber layers into a whole, and the parts that have not been pressed will not be affected, which can avoid the problem of using adhesive composite to reduce the dust holding capacity and liquid absorption performance of the 3D filter material.

[0005] The specific technical scheme of the present invention is: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises a plurality of stacked fiber layers, and the composite end is made by hot-pressing and compounding the fiber layers.

[0006] The present invention provides a 3D filter material, which includes a composite end and a filter end adjacent to the composite end, wherein the filter end is made of a plurality of stacked fiber layers, and the composite end is made by hot pressing and compounding the fiber layers. The material is not compounded using an adhesive, and has an increased dust holding capacity and significantly improved washing liquid performance.

[0007] A method for preparing the above-mentioned 3D filter material comprises the following steps: laminating the fiber layers and then using a pattern roller to hot press and compound to form the 3D filter material, wherein the temperature of the hot pressing and compounding is 50-200°C.

[0008] The present invention provides a method for preparing the above-mentioned 3D filter material, which uses a pattern roller to hot-press and composite the stacked fiber layers. The raised portion of the pattern roller heats and presses the fiber layers to form a composite end, while the recessed portion of the pattern roller does not press the fiber layers so that the volume of the stacked fiber layers is not affected. The present application composites materials with different properties after heating and pressing, thereby avoiding the problem that adhesive composites will reduce the dust holding capacity and liquid absorption performance of the 3D filter material.

[0009] Preferably, the material of the fiber layer includes one or more of a PBT fiber layer, a PP fiber layer and a natural fiber layer.

[0010] Preferably, the PBT fiber layer is made by melt spinning of PBT resin, which is made by copolymerization of terephthalic acid and 1,4-butanediol as raw materials under the conditions of a modifier and a catalyst, and the copolymerization reaction includes esterification, prepolymerization and condensation reaction in sequence.

[0011] Preferably, the modifier is a dibasic acid, a diol and acrylic acid.

[0012] Preferably, the molar ratio of the dibasic acid, diol and acrylic acid is 1:2-2.5:1-2.

[0013] Preferably, the dibasic acid is one or both of isophthalic acid and adipic acid, and the diol is hexanediol.

[0014] The present invention modifies PBT polyester, and the melting point of the modified PBT fiber is reduced to 150-160°C. When the PBT fiber layer and the PP fiber layer made of PBT polyester are hot-pressed and laminated to form a 3D filter material, the PBT fiber layer and the PP fiber melt to form a whole having excellent compatibility, which can significantly reduce the pressing area while ensuring that the composite strength of the 3D filter material meets the standard, significantly increase the volume of the filter end, significantly improve the dust holding capacity of the 3D filter material, and improve the liquid absorption performance of the material. The modifier of the present invention uses dibasic acid, diol and acrylic acid. Adding dibasic acid and diol in the PBT copolymerization synthesis stage can introduce a flexible segment into the PBT copolyester molecular chain to reduce the melting point of PBT, make the melting point of PBT close to the melting point of PP, and enable the fiber layer to quickly melt and composite under low temperature conditions near 150°C. In addition, the present invention finds that adding and then adding acrylic acid can increase the compatibility of PBT and PP, so that the composite strength of PBT and PP after composite is significantly improved.

[0015] Preferably, the molar ratio of terephthalic acid to 1,4-butanediol is 1.3-1.8:2.6-3.

[0016] Preferably, the catalyst is one or more of tetrabutyl titanate, isopropyl titanate, and ethylene glycol titanium.

[0017] Preferably, the conditions of the esterification reaction include: a first-stage esterification reaction temperature of 160-190°C, a first-stage esterification reaction time of 1-3h, a second-stage esterification reaction temperature of 190-220°C, and a second-stage esterification reaction time of 1-2h; the conditions of the prepolymerization reaction include: a first-stage prepolymerization reaction temperature of 220-240°C, a first-stage prepolymerization reaction time of 0.5-1h, a first-stage prepolymerization reaction pressure of 1-10KPa, a second-stage prepolymerization reaction temperature of 240-250°C, a second-stage prepolymerization reaction time of 0.5-1h, and a second-stage prepolymerization reaction pressure of 0.5-1KPa; the conditions of the polycondensation reaction include: a polycondensation reaction temperature of 250-270°C, a polycondensation reaction pressure of 0.01-0.1KPa, and a polycondensation reaction time of 1.5-3h.

[0018] Compared with the prior art, this application has the following technical effects: The present invention provides a 3D filter material and a preparation method thereof. The material comprises a composite end and a filter end adjacent to the composite end. The composite end is made by hot pressing and composites multiple fiber layers into a whole. The unpressed parts will not be affected, and the problem of reducing the dust holding capacity and liquid absorption performance of the 3D filter material by using adhesive composite can be avoided. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the embodiments.

[0020] Embodiment 1: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PP polyester fibers, filter paper fibers and PP polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: PP polyester is made into PP meltblown cloth by meltblowing method, holes are cut on the surface of filter paper to make an intermediate layer, and then the PP meltblown cloth, the intermediate layer and the PP meltblown cloth are overlapped to make a preform, and then the preform is hot-pressed and compounded by a flower roller, the hot-pressing point is located at the hole of the intermediate layer, the hot-pressing temperature is 130°C, and the hot-pressing is completed to make a 3D filter material.

[0021] Embodiment 2: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PP polyester fibers, absorbent paper and PP polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: The PP polyester is made into PP meltblown cloth by meltblowing method, holes are cut on the surface of absorbent paper to make an intermediate layer, and then the PP meltblown cloth, the intermediate layer and the PP meltblown cloth are overlapped to make a preform, and then the preform is hot-pressed and compounded by a flower roller, the hot-pressing point is located at the hole of the intermediate layer, the hot-pressing temperature is 50°C, and the hot-pressing is completed to make a 3D filter material.

[0022] Embodiment 3: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol, 36.03g of acrylic acid and 0.34g of tetrabutyl titanate are added into a reactor for polymerization reaction to prepare PBT polyester, nitrogen is filled into the reactor to evacuate the air in the reactor and the pressure is increased to 0.1MPa, the polymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence; the esterification reaction process is: heating to 160-190°C for a first stage of esterification reaction and reacting for 1-3 h, then heating to 160-190°C for a second-stage esterification reaction and reacting for 1-2h; after the esterification reaction is completed, a prepolymerization reaction is carried out, and the prepolymerization reaction process includes: heating to 220-240°C for a first-stage prepolymerization reaction and reacting for 0.5-1h, then heating to 240-250°C and then increasing the pressure to 0.5-1KPa for a second-stage prepolymerization reaction and reacting for 0.1-1h; after the prepolymerization reaction is completed, a condensation reaction is carried out, and the condensation reaction conditions are: heating to 250-270°C and reducing the pressure to 0.01-0.1KPa for a condensation reaction and reacting for 1.5-3h; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot pressing temperature is 170°C, the hot pressing area accounts for 0.5%, and then cooled and rolled into 3D filter material.

[0023] Embodiment 4: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 47.2g of hexanediol, 72.06g of acrylic acid and 0.34g of tetrabutyl titanate are added into a reactor for polymerization reaction to prepare PBT polyester, nitrogen is filled into the reactor to evacuate the air in the reactor and the pressure is increased to 0.1MPa, the polymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence; the esterification reaction process is: heating to 160-190°C for a first stage of esterification reaction and reacting for 1-2 hours; 3h, then heating to 160-190℃ for two-stage esterification reaction and reacting for 1-2h; after the esterification reaction is completed, prepolymerization reaction is carried out, and the prepolymerization reaction process includes: heating to 220-240℃ for one-stage prepolymerization reaction and reacting for 0.5-1h, then heating to 240-250℃ and then increasing the pressure to 0.5-1KPa for two-stage prepolymerization reaction and reacting for 0.1-1h; after the prepolymerization reaction is completed, polycondensation reaction is carried out, and the polycondensation reaction conditions are: heating to 250-270℃ and reducing the pressure to 0.01-0.1KPa for polycondensation reaction and reacting for 1.5-3h; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot pressing temperature is 170°C, the hot pressing area accounts for 0.3%, and then cooled and rolled to form a 3D filter material.

[0024] Embodiment 5: A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 52.44g of hexanediol, 48.04g of acrylic acid and 0.34g of tetrabutyl titanate were added into a reactor for polymerization reaction to prepare PBT polyester, nitrogen was filled into the reactor to evacuate the air in the reactor and the pressure was increased to 0.1MPa, the polymerization reaction sequentially included esterification reaction, prepolymerization reaction and polycondensation reaction; the esterification reaction process was: heating to 160-190°C for a first stage of esterification reaction and reacting for 1 ~3h, then heating to 160~190℃ for two-stage esterification reaction and reacting for 1~2h; after the esterification reaction is completed, prepolymerization reaction is carried out, and the prepolymerization reaction process includes: heating to 220~240℃ for one-stage prepolymerization reaction and reacting for 0.5~1h, then heating to 240~250℃ and then increasing the pressure to 0.5~1KPa for two-stage prepolymerization reaction and reacting for 0.~1h; after the prepolymerization reaction is completed, polycondensation reaction is carried out, and the polycondensation reaction conditions are: heating to 250~270℃ and reducing the pressure to 0.01~0.1KPa for polycondensation reaction and reacting for 1.5~3h; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot pressing temperature is 170°C, the hot pressing area accounts for 0.1%, and cooled and rolled to form a 3D filter material.

[0025] Comparative Example 1: Compared with Example 1, in Example 1, the fiber layer is compounded with an adhesive, and the amount of adhesive applied is 0.2 g / m 2 .

[0026] Comparative Example 2: Compared with Example 2, in Comparative Example 1, the fiber layer is compounded with an adhesive, and the amount of adhesive applied is 0.2 g / m 2 .

[0027] Comparative Example 3: Compared with Examples 3 to 5, in Example 3, the fiber layer is compounded with an adhesive, and the amount of adhesive applied is 0.2 g / m 2 .

[0028] Comparative Example 4: Compared with Examples 3 to 5, in Comparative Example 4, PBT was not modified, and the hot pressing area accounted for 30%.

[0029] A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid and 0.34g of tetrabutyl titanate are added to a reactor for polymerization reaction to prepare PBT polyester. Nitrogen is filled into the reactor to exhaust the air in the reactor and the pressure is increased to 0.1MPa. The polymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence. The esterification reaction process is: heating to 160-190°C for a stage of esterification reaction and reacting for 1-3h, and then heating to 160-190°C A two-stage esterification reaction is carried out and the reaction lasts for 1 to 2 hours; a prepolymerization reaction is carried out after the esterification reaction is completed, and the prepolymerization reaction process includes: heating to 220 to 240° C. for a first-stage prepolymerization reaction and reacting for 0.5 to 1 hour, then heating to 240 to 250° C. and then increasing the pressure to 0.5 to 1 KPa for a second-stage prepolymerization reaction and reacting for 0. to 1 hour; after the prepolymerization reaction is completed, a polycondensation reaction is carried out, and the polycondensation reaction conditions are: heating to 250 to 270° C. and reducing the pressure to 0.01 to 0.1 KPa for a polycondensation reaction and reacting for 1.5 to 3 hours; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot pressing temperature is 170°C, the hot pressing area accounts for 30%, and then cooled and rolled to form a 3D filter material.

[0030] Comparative Example 5: Compared with Examples 3 to 5, the modifier in Comparative Example 5 does not contain acrylic acid, and the hot pressing area accounts for 5%.

[0031] A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol and 0.34g of tetrabutyl titanate are added to a reactor for polymerization reaction to prepare PBT polyester. Nitrogen is filled into the reactor to evacuate the air in the reactor and the pressure is increased to 0.1MPa. The polymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence. The esterification reaction process is: heating to 160-190°C for a stage of esterification reaction and reacting for 1-3h, then heating to 400°C for 2 hours. to 160-190°C for a two-stage esterification reaction and react for 1-2 hours; after the esterification reaction is completed, a prepolymerization reaction is carried out, and the prepolymerization reaction process includes: heating to 220-240°C for a first-stage prepolymerization reaction and reacting for 0.5-1 hour, then heating to 240-250°C and then increasing the pressure to 0.5-1KPa for a second-stage prepolymerization reaction and reacting for 0.1-1 hour; after the prepolymerization reaction is completed, a condensation reaction is carried out, and the condensation reaction conditions are: heating to 250-270°C and reducing the pressure to 0.01-0.1KPa for a condensation reaction and reacting for 1.5-3 hours; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot pressing temperature is 170°C, the hot pressing area accounts for 5%, and then cooled and rolled to form a 3D filter material.

[0032] Comparative Example 6: Compared with Examples 3 to 5, the modifier in Comparative Example 6 does not contain acrylic acid, and the hot pressing area accounts for 1%.

[0033] A 3D filter material comprises a composite end and a filter end adjacent to the composite end, wherein the filter end comprises PBT polyester fibers, PP polyester fibers and PBT polyester fibers stacked in sequence, and the composite end is made by hot-pressing and compounding fiber layers; A method for preparing the above 3D filter material comprises the following steps: Preparation of PBT polyester: 270g of 1,4-butanediol, 300g of terephthalic acid, 130g of adipic acid, 80g of isophthalic acid, 59g of hexanediol and 0.34g of tetrabutyl titanate are added to a reactor for polymerization reaction to prepare PBT polyester. Nitrogen is filled into the reactor to evacuate the air in the reactor and the pressure is increased to 0.1MPa. The polymerization reaction includes esterification reaction, prepolymerization reaction and polycondensation reaction in sequence. The esterification reaction process is: heating to 160-190°C for a stage of esterification reaction and reacting for 1-3h, then heating to 400°C for 2 hours. to 160-190°C for a two-stage esterification reaction and react for 1-2 hours; after the esterification reaction is completed, a prepolymerization reaction is carried out, and the prepolymerization reaction process includes: heating to 220-240°C for a first-stage prepolymerization reaction and reacting for 0.5-1 hour, then heating to 240-250°C and then increasing the pressure to 0.5-1KPa for a second-stage prepolymerization reaction and reacting for 0.1-1 hour; after the prepolymerization reaction is completed, a condensation reaction is carried out, and the condensation reaction conditions are: heating to 250-270°C and reducing the pressure to 0.01-0.1KPa for a condensation reaction and reacting for 1.5-3 hours; Preparation of 3D filter material: The PBT polyester is made into PBT meltblown cloth by meltblowing method, and the PP polyester is made into PP meltblown cloth by meltblowing method, and the PBT meltblown cloth, PP meltblown cloth and PBT meltblown cloth are stacked in sequence to form a preform, and then the preform is hot-pressed and compounded using a flower roller, the hot-pressing temperature is 170°C, the hot-pressing area accounts for 1%, and then cooled and rolled to form a 3D filter material.

[0034] Test example The 3D filter materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested, and the test items were: peel strength and dust holding capacity; Dust holding capacity test method: Cut the 3D filter material into samples with a length of 100mm and a width of 100mm, weigh the initial weight of the sample, place the sample in the test liquid for 5 minutes, take it out and place it on a mesh water platform for 1 minute to measure the moisture absorption weight. The dust holding capacity is the difference between the moisture absorption weight and the initial weight, in g; The glass strength test method refers to "GB 8808-88 Peeling Test Method for Soft Composite Plastic Materials"; the test steps include: removing 50mm from both ends of the sample in the width direction, evenly cutting 5 longitudinal and transverse specimens along the width direction of the sample, with the composite direction being the longitudinal direction, pre-peeling the composite layer 50mm along the length direction of the sample, and the peeled part shall not have obvious damage. The sample shall be placed in an environment of 23±2℃ and relative humidity of 45-55% for more than 4 hours, and then tested in this environment, and the two ends of the peeled part of the sample are clamped on the upper and lower fixtures of the testing machine respectively, so that the longitudinal axis of the peeled part of the sample coincides with the center line of the upper and lower fixtures, and the tightness is appropriate, and the unpeeled part is T-shaped with the tensile direction to record the peeling curve of the glass process, and the test speed is 200±50mm / min; the arithmetic mean value of each group of samples is calculated in N.

[0035] The test results are shown in Table 1; Table 1 Test results As shown in Table 1, in Examples 1 to 2, the middle layer is punched, and then the fiber layer is hot-pressed and composited at the punched position of the middle layer. The peel strength of Examples 1 to 2 is 10-12N, and the dust holding capacity is 253-563g. Comparative Examples 1 to 2 are materials composited using adhesives, and the peel strength of Comparative Examples 1 to 2 is only 4-5N, and the dust holding capacity is only 181-430g. The above results show that after the middle layer of the 3D material of the present application is punched, the fiber layers of the same material on both sides of the two middle layers can be bonded, and the materials of the same material have better compatibility after hot-pressing composite. Therefore, the composite strength of the material can be significantly improved after hot pressing, which is significantly higher than that of the material using adhesives.

[0036] In addition, the present application has found that the method of punching and then compounding has a great influence on the hot pressing compounding area. The size of the holes has high requirements on the accuracy of the material and the punching device. At the same time, it is also necessary to provide a flower roller corresponding to the holes. The process is relatively complicated, and the hole diameter of the holes is usually larger, resulting in a larger hot pressing compounding area and a dust holding capacity of the handover material. Therefore, Examples 3 to 5 are provided on the basis of the above content.

[0037] In Examples 3 to 5, modified PBT polyester and PP polyester are used to make 3D materials. PP polyester is used as the middle layer, and the modified PBT polyester is located between the two middle layers. The modified PBT polyester is a low-melting-point PBT polyester modified by a modifier and has excellent compatibility with PP polyester. During hot-pressing composite, the PBT fiber and the PP fiber will melt at the same time and become a whole. Compared with the ordinary composite interface, the composite strength is significantly improved.

[0038] Comparative Example 3 is a 3D filter material using an adhesive, and its peel strength is only 6N, and the dust holding capacity is only 258g, which is significantly lower than Examples 3 to 5 (the peel strength is only 15-18N, and the dust holding capacity is only 292-311g). The above results show that the 3D filter material provided by the present invention is comparable to the adhesive composite method and can significantly improve the composite strength and dust holding capacity of the 3D filter material.

[0039] In Comparative Example 4, no modifier was used for PBT, and its peel strength was only 7N, and its dust holding capacity was only 203g, which were significantly lower than those in Examples 3 to 5. After analysis, it was found that the melting temperature of PBT polyester without a modifier was higher. Therefore, when the fiber was compounded at a hot pressing temperature of 150°C, only the PP polyester would melt, but the PBT polyester would not melt. After the PP polyester melted, it was solidified and compounded with the PBT fiber. Since the compatibility between PP polyester and unmodified PBT polyester was poor, the hot pressing area needed to be increased to 30% to achieve a peel strength of 7N for the material, but the dust holding capacity would drop to 203g, which was significantly reduced.

[0040] In Comparative Example 5, no acrylic acid was added to the modifier. When the hot pressing area of ​​Comparative Example 5 reached 5%, its peel strength reached 6N and the dust holding capacity was 286g. Although the PBT polyester was modified into a low-melting-point PBT polyester, the PBT fiber and the PP fiber could be melted at the same time to form a more compact structure, the composite strength of the material formed after the two were melted and mixed was still low due to the poor compatibility of the PBT polyester and the PP polyester. The hot pressing area still needed to reach more than 5% to have a good composite strength. The dust holding capacity and composite strength were still significantly lower than those of Examples 3 to 5. In Comparative Example 6, no acrylic acid was added to the modifier. When the hot pressing area was reduced to 1%, the peel strength was only 3N, and the peel strength was significantly reduced. After combining Comparative Example 5, Comparative Example 6 and Examples 3 to 5, it was found that the PBT polyester and PP The composite strength of the composite formed by melting and mixing polyesters at the same time is higher than the composite strength of the composite interface formed by PBT fiber and PP polyester. The composite interface needs to increase the area of ​​the composite interface to improve the composite strength, and the increase in the area of ​​the composite interface will lead to a decrease in the dust holding capacity of the material. Therefore, the composite formed by the melting of the materials can ensure the composite strength while reducing the composite area to increase the dust holding capacity of the material. The composite strength of the composite is closely related to the compatibility of the fiber material. The higher the compatibility, the higher the composite strength of the formed composite. Therefore, improving the compatibility of the fiber material can significantly improve the composite strength of the composite formed by hot pressing. Therefore, it is possible to significantly reduce the composite area while ensuring the composite strength of the 3D material, thereby significantly improving the dust holding capacity of the material, so that the 3D material has both high composite strength and high dust holding performance.

[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A 3D filter material, characterized in that: It comprises a composite end and a filtering end adjacent to the composite end, wherein the filtering end comprises a plurality of stacked fiber layers, and the composite end is made by hot-pressing and compounding the fiber layers.

2. A method for preparing the 3D filter material according to claim 1, characterized in that: The following steps are involved: After the fiber layers are stacked, they are hot-pressed and compounded using a flower roller to form a 3D filter material. The temperature of the hot-pressing compound is 50~200 ℃.

3. The preparation method according to claim 2, characterized in that: The material of the fiber layer includes one or more of a PBT fiber layer, a PP fiber layer and a natural fiber layer.

4. The preparation method according to claim 3, characterized in that: The PBT fiber layer is made by melt spinning of PBT resin, and the PBT resin is made by copolymerization of terephthalic acid and 1,4-butanediol as raw materials under the conditions of modifier and catalyst, and the copolymerization reaction includes esterification reaction, prepolymerization reaction and condensation reaction in sequence.

5. The preparation method according to claim 4, characterized in that: The modifiers are dibasic acid, diol and acrylic acid.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the dibasic acid, the diol and the acrylic acid in the modifier is 1:2-2.5:1-2.

7. The preparation method according to claim 5 or 6, characterized in that: The dibasic acid is one or both of isophthalic acid and adipic acid, and the diol is hexanediol.

8. The preparation method according to claim 4, characterized in that: The molar ratio of terephthalic acid to 1,4-butanediol is 1.3-1.8:2.6-3.

9. The preparation method according to claim 4, characterized in that: The catalyst is one or more of tetrabutyl titanate, isopropyl titanate and ethylene glycol titanium.

10. The preparation method according to claim 4, characterized in that: The conditions of the esterification reaction include: a first-stage esterification reaction temperature of 160-190°C, a first-stage esterification reaction time of 1-3 h, a second-stage esterification reaction temperature of 190-220°C, and a second-stage esterification reaction time of 1-2 h; the conditions of the prepolymerization reaction include: a first-stage prepolymerization reaction temperature of 220-240°C, a first-stage prepolymerization reaction time of 0.5-1 h, a first-stage prepolymerization reaction pressure of 1-10 KPa, a second-stage prepolymerization reaction temperature of 240-250°C, a second-stage prepolymerization reaction time of 0.5-1 h, and a second-stage prepolymerization reaction pressure of 0.5-1 KPa; the conditions of the polycondensation reaction include: a polycondensation reaction temperature of 250-270°C, a polycondensation reaction pressure of 0.01-0.1 KPa, and a polycondensation reaction time of 1.5-3 h.

Citation Information

Patent Citations

  • Wiping cloth used for industry

    CN102162173B

  • Wiping cloth manufacturing method and wiping cloth

    CN112726058A

  • Method of manufacturing a composite filter media

    CN102112197A

  • Composite material using stretchable nonwoven fabric

    CN102211426A

  • Non-woven fiber fabric, and production method and production device therefor

    CN103038407A